The effect of modified bacterial virulence to host-pathogen relationship (Phaseolus vulgaris L. Pseudomonas savastanoi pv. phaseolicola) - A. Végvári; M. Hevesi; É. Sárdi; J. Szarka; I. Velich (International Journal of Horticultural Science, 1999)
The Pseudomonas savastanoi pv. phaseolicola is one of the most expressive biogen stressors of the bean (Phaseolus vulgaris L.) in Hungary. The chemical and agrotechnological defence is inefficient, so breeding is the only workable way. The conventional cultivars are susceptible to PS while most of the new industrial varieties have genetic resistance to the pathogen. The genetic background of resistance is, however, a complex system in the bean. Leaf resistance is a monogenic system, but this gene is not expressed in juvenile stage of the host. The pathogen species can be divided into different races. After inoculation with virulent strains, typical symptoms appeared on the leaves. To understand the details of host-pathogen relationships, there were carried out experiments using bacterial strains with altered virulence. Six transposon mutants of the PS were tested. Our main objective was to test these modified bacterial strains on bean cultivars of known genetic background. First we analysed the symptoms, and then the correlation between the symptoms and the multiplication of mutant bacteria. Three cultivars (Cherokee, Inka and Főnix) were tested.